Steam Influence and Effect of Oxidant Amount on Propane Oxidation over Multi Metal Oxide Catalyst Using High-Throughput Experiment - Restu Kartiko Widi; Sharifah Bee Abd Hamid (Universitas Gadjah Mada, 2018)
The high-throughput experimentation technique was used to verify the testing conditions due to the effects of catalyst structure modifications and/or due to reaction parameter variation in parallel. In this paper, the design of experiment and catalytic results are discussed in the development of selective oxidation catalyst, to demonstrate the importance and versatility of such technology. It is used for the automated parallel testing of selective oxidation of propane to acrylic acid over some types of multi metal oxide catalysts. The catalysts used for performance test were Mo (molybdenum), cat-1 (unsupported Mo1V0.3Te0.23Nb0.125O), and cat-2 (supported Mo1V0.3Te0.23Nb0.125O). All catalysts were dried using spray drier. The effect of some reaction parameters, such as the amount of oxidant, presence of steam and reaction temperature was also investigated during the test. The configuration of the ‘nanoflow’ is shown to be suitable to screen catalytic performance. The results obtained gave very good reproducibility.